If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 57 + -6x = 3x + 17 Reorder the terms: 57 + -6x = 17 + 3x Solving 57 + -6x = 17 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 57 + -6x + -3x = 17 + 3x + -3x Combine like terms: -6x + -3x = -9x 57 + -9x = 17 + 3x + -3x Combine like terms: 3x + -3x = 0 57 + -9x = 17 + 0 57 + -9x = 17 Add '-57' to each side of the equation. 57 + -57 + -9x = 17 + -57 Combine like terms: 57 + -57 = 0 0 + -9x = 17 + -57 -9x = 17 + -57 Combine like terms: 17 + -57 = -40 -9x = -40 Divide each side by '-9'. x = 4.444444444 Simplifying x = 4.444444444
| 106-4x=14x+18 | | 6x+166=13x-9 | | 9-9x=132-30x | | 4x-2=2x+4 | | 4x+x+5x=30 | | y+7=30 | | 5y+4(y-7)=4(y+2)-5 | | -122-8x=10x+22 | | 8x^2+14x=-3 | | 1.5+3.6+0.3n=-1 | | 2y+6=8 | | -122-8x=132-30x | | 10m+3n-6m+11n= | | 4x^2+30=330 | | 5x+7=-35-9x | | -5(t-3)+8t=6t+-7 | | 0.5h-3=19 | | 4(4x+4)+3=16x+19 | | -23-6x=9-10x | | 6x-5=6(x-7) | | f(-x)=4x^2+2x+8 | | 12x+19=2x-9 | | 3(x-2)+6=4 | | 0.60x+0.30(80)=0.30(134) | | -x=39 | | -4x+3=8x+21 | | 11x+6=7+18 | | 18x-32=-23x-6 | | 4k=k+12 | | 4x+38=12x-42 | | 3x-6=2x+4 | | -x^2-8x-19=0 |